Model to predict survival after surgical resection of intrahepatic cholangiocarcinoma: the Mayo Clinic experience. Issue 3 (March 2015) - Ali, Shahzad M.; Clark, Clancy J.; Mounajjed, Taofic; Wu, Tsung‐Teh; Harmsen, William S.; Reid‐Lombardo, KMarie; Truty, Mark J.; Kendrick, Michael L.; Farnell, Michael B.; Nagorney, David M.; Que, Florencia G.
Abstract: Background: The 7th edition of the American Joint Committee on Cancer (AJCC) staging system has recently been validated and shown to predict survival in patients with intrahepatic cholangiocarcinoma (ICC). The present study attempted to investigate the validity of these findings. Methods: A single‐centre, retrospective cohort study was conducted. Histopathological restaging of disease subsequent to primary surgical resection was carried out in all consecutive ICC patients. Overall survival was compared using Kaplan–Meier estimates and log‐rank tests. Results: A total of 150 patients underwent surgery, 126 (84%) of whom met the present study's inclusion criteria. Of these 126 patients, 68 (54%) were female. The median length of follow‐up was 4.5 years. The median patient age was 58 years (range: 24–79 years). Median body mass index was 27 kg/m 2 (range: 17–46 kg/m 2 ). Staging according to the AJCC 7th edition categorized 33 (26%) patients with stage I disease, 27 (21%) with stage II disease, five (4%) with stage III disease, and 61 (48%) with stage IVa disease. The AJCC 7th edition failed to accurately stratify survival in the current cohort; analysis revealed significantly worse survival in those with microvascular invasion, tumour size of >5 cm, grade 4 disease, multiple tumours and positive lymph nodes ( P < 0.001). A negative resection margin was associated with improved survival ( P < 0.001). Conclusions: The AJCC 7th edition did not accurately predict survival in patients with ICC. A multivariable model including tumour size and differentiation in addition to the criteria used in the AJCC 7th edition may offer a more accurate method of predicting survival in patients with ICC.